SYSTEMATIC REVIEW OF DIAGNOSIS AND MANAGEMENT OF VIRUS INFECTIONS IN PREGNANCY: CLINICAL IMPLICATIONS AND INTEGRATED INTERVENTION STRATEGIES - Zelia Maria da Silva (Jurnal Kesehatan Karya Husada, 2025)
Viral infections during pregnancy are one of the main challenges in maternal and neonatal health because they can cause obstetric complications, fetal development disorders, and increased mortality. This study aims to systematically review the diagnosis, management, and intervention strategies for viral infections in pregnancy through an analysis of the latest international research results. A search was conducted on seven scientific articles published in 2021–2024, covering studies on HIV, Zika, Cytomegalovirus (CMV), and Influenza. The analysis method used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. The synthesis results show that maternal infection increases the risk of miscarriage, premature birth, fetal neurological disorders, and vertical transmission. Monitoring maternal viral load and antibodies are key indicators for detecting the risk of infection in the fetus, while reproductive health education and the integration of antenatal–postnatal services strengthen the effectiveness of prevention. An integrated approach combining biomedical, educational, and public policy aspects has been shown to improve the effectiveness of diagnosis and management. This study emphasizes the importance of multidisciplinary collaboration and the need for mother-child longitudinal studies to understand the long-term effects of infection exposure on neurocognitive development and chronic health. Keywords: viral infection, pregnancy, vertical transmission, early diagnosis, integrated intervention, maternal health.